When peacekeeping missions collide : balancing multiple roles in peace operations - Diehl, Paul F. (Paul Francis); Druckman, Daniel, 1939-; Mueller, Grace B. (New York, NY : Oxford University Press, 2024)
"Most analyses of peacekeeping focus on attempts to limit violent conflict. Yet contemporary peace operations are asked to do much more, including unconventional roles of monitoring elections, facilitating transitions to the rule of law, distributing humanitarian aid, and resolving conflicts in civil societies undergoing transformation. This path-breaking work takes the lid off peace operations to explore missions (e.g., Disarmament, Demobilization, and Reintegration) that go beyond traditional peacekeeping and the ways mission outcomes influence one another. This work begins by documenting patterns of peacekeeping missions in 70 UN operations, noting the dramatic increase in number and diversity since the end of the Cold War and the shift to conflicts with a substantial internal conflict component. The core of the book examines eight expectations about how different missions interact with one another. The expectations are guided by theoretical logics associated with sequencing, compatibility, and multitasking. These are examined in five detailed case studies of UN operations: United Nations Protection Force or UNPROFOR (Bosnia); United Nations Operation in the Congo or ONUC (Congo); United Nations Transitional Administration in East Timor or UNTAET (East Timor); United Nations Organization Mission in the Democratic Republic of the Congo or MONUC (Congo); and the United Nations Mission in Sierra Leone or UNAMSIL (Sierra Leone). The final chapter reviews the findings in terms of their implications for the expectations. It also provides a policy-relevant framework for organizing the various parts and stages of a peace operation, offering a future research agenda on multiple mission peacekeeping"--
The puzzle of multiple missions -- Patterns in multi-mission peace operations and theoretical expectations -- Research plan -- Limited mission cases : ONUC and UNPROFOR -- Complex mission cases : UNTAET and MONUC -- The United Nations mission in Sierra Leone (UNAMSIL) -- Conclusions and implications.
Includes bibliographical references (pages 257-288) and index.
Keywords: United Nations -- Peacekeeping forces -- Case studies; Strategy -- Case studies; Conflict management -- Case studies; Case studies